Developing cultures : case studies - Harrison, Lawrence E.; Berger, Peter L., 1929-2017.; Harrison, Lawrence E. (New York : Routledge, 2006)
A companion volume to "Developing Cultures: Essays on Cultural Change", this is a collection of case-studies by leading scholars on the role of culture and cultural change in the development of countries and regions around the world. These thinkers approach the role of culture from various angles
CONTENTS: Introduction / Lawrence E. Harrison -- Some reflections on culture and development / Peter L. Berger -- PART I. AFRICA -- Explaining Botswana's success / Stephen R. Lewis, Jr. -- Culture and development: questions from South Africa / Ann Bernstein -- Culture of development in a southwestern Nigerian town / Elisha P. Renne -- PART II. CONFUCIAN COUNTRIES -- China's cultural renaissance / Tu Weiming -- Japanese culture and postwar economic growth / Yoshihara Kunio -- Values and development in Singapore / Chua Beng-Huat -- Market development, political change, and Taiwanese cultures / Robert P. Weller -- PART III. INDIA -- India: how a rich nation became poor and will be rich again / Gurcharan Das -- PART IV. ISLAM -- Egypt as a model of development for the world of Islam / Bassam Tibi -- Cultural matters and developmental dilemmas in Indonesia / Robert W. Hefner -- Two halves did not make a whole: Pakistan before and after Bangladesh / F.S. Aijazuddin, with a response by Adil Najam -- Turkey: torn between two civilizations / Yilmaz Esmer -- PART V. LATIN AMERICA -- The political values of development: the case of Argentina / Mariano Grondona -- Importance of culture: the Brazilian case / Maria Lucia Victor Barbosa -- Economic development and the evolution of national culture: the case of Chile / David E. Hojman -- Mexico: the camel and the needle / Miguel Basáñez -- Productive values and poverty in Venezuela / Luis Ugalde -- PART VI. ORTHODOX / EASTERN EUROPE -- Which past matters? Culture and economic development in Eastern Europe after 1989 / Janos Matyas Kovacs -- Timeless identity versus another final modernity: identity master myth and social change in Georgia / Irakli Chkonia -- Tale of two regions: Novgorod and Pskov as models of symbolic development / Nicolai N. Petro -- Cultural change and continuity in the transition from communism: the Russian case / Archie Brown -- PART VII. THE WEST -- Scene from a fast-food restaurant: signs of the times in black America and the path beyond / John McWhorter -- Ireland as the Celtic tiger: how did it happen? / Dick Spring -- Long and winding road: the Italian path to modernization / Matteo B. Marini -- Culture and the pursuit of success: the case of Québec in the twentieth century / Daniel Latouche -- Spanish transition: 1975-82 / Carlos Alberto Montaner -- Strong governance and civic participation: some notes on the cultural dimension of the Swedish model / Dag Blanck, Thorleif Pettersson.
Includes bibliographical references and index.
Keywords: Acculturation -- Case studies; Cultural lag -- Case studies; Economic development -- Case studies; Progress -- Case studies; Social change -- Case studies; Social values -- Case studies; Developing countries -- Case studies